Effect of vegetarian diets on performance in strength sports - Forbes-Ewan, C. (Sportscience, 2002)
A lacto-ovovegetarian diet can provide all the nutrients required for optimal health. Anecdotal reports suggest that many successful endurance athletes are vegetarians whereas few reports suggest that elite strength athletes follow a vegetarian diet. Strength and power athletes almost invariably include meat in their diets, although it is unclear whether the benefits of meat consumption for strength and power are real or imagined.